Effect of shot peening on surface properties of Al7075 hybrid aluminum metal matrix composites. (2020) - Sasikumar, K.S.K.; Dineshkumar, K.; Deeban, K.; Sambathkumar, M.; Saravanan, N.
Abstract: Various fields of engineering such as automobile, aerospace and construction industries are employs Aluminum alloys and its composites due to its high strength to weight ratio. But they possess poor wear resistance due to low hardness. In this research, shot peening treatment is used to enhance the wear resistance ability of the composites. Micro hardness and surface roughness of AL7075 Hybrid metal matrix composites are examined after shot peening treatment. For this, the aluminum alloy specimens are subjected to shot peening for 30, 60, 90, 120 and 150 s time. The results reveal that the shot peening treatment increases micro -hardness and surface roughness up to 90 s. The specimen after 120 s peening demonstrates the marginal improvement in micro hardness and slight reduction in surface roughness.